Clinical researchChanges in clinical and metabolic parameters after exercise therapy in patients with type 2 diabetes - Gordon, Lorenzo; Morrison, Errol Y.; McGrowder, Donovan A.; Young, Ronald; Garwood, David; Zamora, Eslaen; Alexander-Lindo, Ruby L.; Irving, Rachael; Perez Sanz, Elsa C. (Archives of Medical Science, 2008)
Introduction: The study was carried out to investigate the effect of Hatha yoga and conventional physical training (PT) exercise intervention on clinical and biochemical parameters in patients with type 2 diabetes. Material and methods: The patient population consisted of 77 type 2 diabetic patients in the Hatha yoga exercise group, matched with the same number of patients in the conventional PT exercise and control groups. The clinical parameters were weekly diastolic and systolic blood pressures, along with body mass index (BMI). Biochemical parameters included weekly blood glucose, serum creatinine, microalbumjinuria and glycosylated haemoglobin (HbA1c) measured at baseline and two consecutive three monthly intervals. Results: There were significant differences in the blood glucose concentrations ”before exercise” and ”after exercise” for the Hatha yoga and conventional PT exercise groups at different weekly intervals (P<0.05). The frequency of signs and symptoms of hypoglycaemia and hyperglycaemia over the weeks during exercise was greater in the conventional PT exercise than in the Hatha yoga exercise group (P=0.004). The HbA1c concentration decreased after six months in the Hatha yoga and conventional PT exercise groups and was significantly different from that of the control group (P<0.05). There were significant reductions in systolic and diastolic blood pressures observed before and after exercise for the Hatha yoga and conventional PT exercise groups (P=0.0001). Conclusions: These findings suggest that better glycaemic and blood pressure control can be obtained in type 2 diabetic patients after Hatha yoga and conventional PT exercises.